Principles of teaching 2 (with TLE) - Corpuz, Brenda B.; Salandanan, Gloria G. (Lorimar Publishing Inc., 2015)
"This book is focused on the goals/outcomes/standards of each subject for each grade in the basic education curriculum. It purposely devoted a number of pages to the program standards, key stage standards and Grade level standards of the subjects in basic education, all of which were necessarily lifted from the K to 12 Curriculum Guide issued by the Department of Education in December 2013."--Preface.